The relationship between organizational development and teacher performance? - Nellitawati, Nellitawati (COUNS-EDU: The International Journal of Counseling and Education, 2019)
This study analyzes the contribution of the principal's organizational development to teacher performance. It uses a descriptive correlational method, with a total sample of 86 teachers. The study used organizational development and teacher performance questionnaires for data collection. The analysis of data were based on partial correlation and multiple linear regression techniques. According to the results, organizational development has a significant influence on teacher performance.